Macrosociology an introduction to human societies - Sanderson, Stephen K. (HarperCollins College Publishers, 1995)
A general sociology text written from a comparative, historical, and evolutionary perspective. The most important changes in this updated edition are a reworked discussion of the rise of modern capitalism and revised and extended discussions of the recent economic and political changes in the former.